Aligning Climate Models With Stakeholder Needs: Advances in Communicating Future Rainfall Uncertainties for South Florida Decision Makers. Issue 7 (7th July 2020) - Infanti, Johnna M.; Kirtman, Ben P.; Aumen, Nicholas G.; Stamm, John; Polsky, Colin
Abstract: Changes in future precipitation are of great importance to climate data users in South Florida. A recent U.S. Geological Survey workshop, "Increasing Confidence in Precipitation Projections for Everglades Restoration, " highlighted a gap between standard climate model outputs and the climate information needs of some key Florida natural resource managers. These natural resource managers (hereafter broadly defined as "climate data users") need more tailored output than is commonly provided by the climate modeling community. This study responds to these user needs by outlining and testing an adaptable methodology to select output from ensemble climate‐model simulations based on user‐defined precipitation drivers, using statistical methods common across scientific disciplines. This methodology is developed to provide a "decision matrix" that guides climate data users to specify the subset of models most important to their work based on each user's season (winter, summer, and annual) and the condition (dry, wet, neutral, and no threshold events) of interest. The decision matrix is intended to better communicate the subset of models best representing precipitation drivers. This information could increase users' confidence in climate models as a resource for natural resource planning and can be used to direct future dynamical downscaling efforts. This methodology is based in dynamical processes controlling precipitation via remote and local teleconnections. We also suggest that future climate studies in South Florida include high‐resolution climate model runs (i.e., ocean eddy resolving) in conjunction with dynamical downscaling to adequately capture precipitation variability. Key Points: A decision matrix for users who wish to determine which model(s) most confidently represent precipitation variability is developed Selection of models we are most confident in based on their representation of the natural driving forces of Florida precipitation This subsetting approach should lead to improvements in how the climate modeling community can better serve natural resource managers